EVALUASI KINERJA PENCAHAYAAN ALAMI TERHADAP STANDAR PENCAHAYAAN RUANG HUNIAN MENGGUNAKAN LUX METER PADA RUMAH TINGGAL DUA LANTAI DI CIKARANG - Chesta Nahda Tigaprilarda; Sutrisno; Chillie Aurora Meydiano; Clara Devina Rizki Alfreda; Clarissya Ayuningtyas; Tee Tze Kiong (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Natural lighting is one of the important factors in improving visual comfort and energy efficiency in residential buildings (Nur et al., 2023). However, in practice, many houses do not meet the recommended lighting standards. This study aims to evaluate the performance of natural lighting in a two-story residential house located in Sukamahi District, Central Cikarang, and to assess its compliance with the SNI 6197:2011 standard (Damayanti & Setiawan, n.d.).The method used in this study is a quantitative approach through direct measurement using a lux meter at several observation points arranged in a grid pattern in each room, with measurement times between 08:00 and 15:00. The collected data were analyzed by comparing illumination values with the applicable minimum lighting standards.The results show that most rooms in the building do not meet the natural lighting standards. The family room on the second floor has the best lighting level, with an illumination range of 142–305 lux, while the living room ranges from 60–236 lux, with only some areas meeting the standard. The second-floor bedroom has moderate lighting with a range of 58–165 lux, whereas the first-floor bedroom and bathroom show low illumination values, ranging from 22–85 lux and 18–39 lux, respectively.These findings indicate that the distribution of natural lighting is strongly influenced by room configuration, the position and dimensions of openings, and the presence of structural obstructions within the building. Therefore, optimization of opening design and spatial layout is necessary to improve natural lighting quality, visual comfort, and energy efficiency in two-story residential houses (Reza et al., n.d.).